Contrast-Enhanced Nanofocus X-Ray Computed Tomography Allows Virtual Three-Dimensional Histopathology and Morphometric Analysis of Osteoarthritis in Small Animal Models. (January 2014) - Kerckhofs, Greet; Sainz, Julie; Maréchal, Marina; Wevers, Martine; Van de Putte, Tom; Geris, Liesbet; Schrooten, Jan
Objective: One of the early hallmarks of osteoarthritis (OA) is a progressive degeneration of the articular cartilage. Early diagnosis of OA-associated cartilage alterations would be beneficial for disease prevention and control, and for the development of disease-modifying treatments. However, early diagnosis is still hampered by a lack of quantifiable readouts in preclinical models. Design : In this study, we have shown the potency of contrast-enhanced nanofocus x-ray computed tomography (CE-nanoCT) to be used for virtual 3-dimensional (3D) histopathology in established mouse models for OA, and we compared with standard histopathology. Results : We showed the equivalence of CE-nanoCT images to histopathology for the modified Mankin scoring of the cartilage structure and quality. Additionally, a limited set of 3D cartilage characteristics measured by CE-nanoCT image analysis in a user-independent and semiautomatic manner, that is, average and maximum of the noncalcified cartilage thickness distribution and loss in glycosaminoglycans, was shown to be predictive for the cartilage quality and structure as can be evaluated by histopathological scoring through the use of an empirical model. Conclusions : We have shown that CE-nanoCT is a tool that allows virtual histopathology and 3D morphological quantification of multitissue systems, such as the chondro-osseous junction. It provides faster and more quantitative data on cartilage structure and quality compared with standard histopathology while eliminating user bias. CE-nanoCT thus should allow capturing subtle differences in cartilage characteristics, carefully mapping OA progression and, ultimately, asses the beneficial changes when testing a candidate disease-modifying treatment.